2016
DOI: 10.1148/radiol.2015150612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Working Memory Performance and Cerebral Activation after Mild Traumatic Brain Injury: A Functional MR Imaging Study

Abstract: The different manifestations of postconcussion symptoms at functional MR imaging between younger and older patients confirmed the important role of age in the activation, modulation, and allocation of WM processing resources after MTBI. These findings also supported that younger patients have better neural plasticity and clinical recovery than do older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…One prospective study of 98 patients across the spectrum of age and TBI severity that performed MRIs, on average, 2.3 years post-TBI identified an association between older age and both larger lesion volumes and smaller gray matter volumes. 106 Emerging neuroimaging technologies for TBI include advanced structural MRI sequences such as diffusion tensor imaging or 7-Tesla MRI, functional MRI, 107 and a number of PET ligands that bind (with varying specificity) to amyloid-beta, tau, and markers of inflammation. 108,109 Using these emerging technologies in older adults deserves further study.…”
mentioning
confidence: 99%
“…One prospective study of 98 patients across the spectrum of age and TBI severity that performed MRIs, on average, 2.3 years post-TBI identified an association between older age and both larger lesion volumes and smaller gray matter volumes. 106 Emerging neuroimaging technologies for TBI include advanced structural MRI sequences such as diffusion tensor imaging or 7-Tesla MRI, functional MRI, 107 and a number of PET ligands that bind (with varying specificity) to amyloid-beta, tau, and markers of inflammation. 108,109 Using these emerging technologies in older adults deserves further study.…”
mentioning
confidence: 99%
“…41 In a recent mTBI study, age-related differences were observed in functional MRI activation in the frontal and parietal brain regions, while performing a working memory task. 27 Younger participants showed hyper-activation of cortical regions while performing a working memory task, which resolved at follow-up. However, elderly patients showed hypo-activation following injury and did not show any improvement at follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…, 41 Persistent symptoms have also been attributed to less cognitive reserve in the elderly 41 . In a recent mTBI study, age-related differences were observed in functional MRI activation in the frontal and parietal brain regions, while performing a working memory task 27 . Younger participants showed hyper-activation of cortical regions while performing a working memory task, which resolved at follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations